Overexpression of Prunus mume Dehydrin Genes in Tobacco Enhances Tolerance to Cold and Drought - Bao, Fei; Du, Dongliang; An, Yang; Yang, Weiru; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2017)
Dehydrins, known as group 2 or D-11 family late-embryogenesis-abundant (LEA) proteins, play important roles in plant growth and stress tolerance. Six dehydrin genes were previously identified from the genome of Prunus mume. In this study, five of them (PmLEA8, PmLEA10, PmLEA19, PmLEA20, and PmLEA29) were cloned from cold-resistant P. mume ‘Beijingyudie’. Real-time RT-PCR analysis indicated that all these genes could be upregulated by one or several treatments (ABA, SA, low temperature, high temperature, PEG, and NaCl treatments). The results of spot assay demonstrated that the expression of all these dehydrins, except PmLEA8, conferred improved osmotic and freezing-resistance to the recombinant Escherichia coli. So four dehydrin genes, PmLEA10, PmLEA19, PmLEA20 and PmLEA29 were chosen for over-expression in tobacco plants individually. The transgenic tobacco plants showed lower relative content of malondialdehyde (MDA), relative electrolyte leakage (REL) and higher relative content of water (RCW) than control plants when exposed to cold and drought stress. These results demonstrated that PmLEAs were involved in plant responses to cold and drought.